2005
DOI: 10.1016/j.accreview.2005.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Peak Oxygen Consumption as a Predictor of Death in Patients With Heart Failure Receiving β-Blockers

Abstract: Background-Peak oxygen uptake (peak V O 2 ) is a strong predictor of mortality and is commonly used in the evaluation of patients for cardiac transplantation. ␤-Blockers reduce mortality in patients with heart failure, without influencing peak V O 2 , raising the possibility that peak V O 2 is no longer suitable as an indicator of prognosis in these patients. Methods and Results-We analyzed prospectively gathered data on 2105 patients referred for cardiopulmonary testing for all-cause mortality and for occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 9 publications
3
50
0
1
Order By: Relevance
“…However, this threshold was proposed prior to the standard use of beta-blocker therapy which has been shown to improve survival without increasing peak VO 2 in HF. As a result, it has been suggested that the peak VO 2 threshold for prognostic purposes be reduced to \/C10 ml O 2 kg -1 min -1 in patients prescribed a betablocking agent [61]. The most commonly cited dichotomous threshold for the VE/VCO 2 slope is \/C34 [15,22,26].…”
Section: Differences In Endpoints Used For Prognostic Investigationsmentioning
confidence: 99%
“…However, this threshold was proposed prior to the standard use of beta-blocker therapy which has been shown to improve survival without increasing peak VO 2 in HF. As a result, it has been suggested that the peak VO 2 threshold for prognostic purposes be reduced to \/C10 ml O 2 kg -1 min -1 in patients prescribed a betablocking agent [61]. The most commonly cited dichotomous threshold for the VE/VCO 2 slope is \/C34 [15,22,26].…”
Section: Differences In Endpoints Used For Prognostic Investigationsmentioning
confidence: 99%
“…Regardless of its aetiology, it is usually characterised by all the features shown in Table 1 [5][6][7][8][9][10].…”
Section: Definitionmentioning
confidence: 99%
“…Nevertheless, there are some concerns about this VE-related parameter, given that a large prospective study conducted by the Cleveland Clinic on 2,015 CHF patients finds that it is not predictive of survival, while a low peak VO 2 value may be an even more powerful predictor in patients receiving b-blocker therapy than in those treated without b-blocker therapy. [2] For all these considerations, we read with interest Scardovì et al's paper entitled ''Prognostic value of brain natriuretic peptide and enhanced ventilatory response to exercise in patients with chronic heart failure'' [3]. Their study, conducted on a sample of 156 consecutive stable CHF outpatients, had an ambitious aim since it attempted to investigate potential additive value of CPET-derived data in CHF prognostic evaluation by developing a multiparametric model including several clinical, echocardiographic and neurohormonal ones.…”
mentioning
confidence: 97%